Miscanthus as energy crop: Environmental assessment of a miscanthus biomass production case study in France. (20th November 2016) - Morandi, F.; Perrin, A.; Østergård, H.
Abstract: The cultivation of miscanthus ( Miscanthus x Giganteus ) as biomass for energy production has increased year by year due to its agronomical performances. In particular, in France, miscanthus is cultivated in the Bourgogne region and it is used as feedstock to produce pellet. In this paper, emergy assessment of different logistic (harvesting) strategies for miscanthus production in the Bourgogne region is presented. Emergy assessment is a particular methodology suited to quantify the resource use of a process and to estimate the percentage of renewability of products or services. The case study includes all phases to grow miscanthus, harvest the biomass as chips or short- or long-stranded bales and distribute it to a bioenergy plant. The aim of this study is to evaluate the sustainability performance of the whole process, from the field to the plant's gate. The emergy flow that represents the environmental cost of the whole process, the percentage of renewability (%R) and the Unit Emergy Values (UEV) that represent the resource use efficiency of the final products for each phase are calculated. Since miscanthus is reproduced by rhizomes, in addition to the system for growing and distributing miscanthus biomass, the system for producing miscanthus rhizomes is also analysed and a UEV for miscanthus rhizomes of 1.19E+05 seJ/J was obtained. Moreover, due the absence of other emergy assessments for miscanthus biomass for comparison, a sensitivity analysis has been made by considering different transport distances and different aboveground biomass yields. Comparing the harvesting methodologies, the bales made with short strands has the best performance. The aboveground biomass production was found to have an Energy Return On energy Investment (EROI), which is the double of that from an experimental miscanthus field in Italy. However, this implied a trade-off for the net energy production of about 50%. Highlights: Results from a case study of miscanthus biomass production for energy purposes. Environmental assessment by emergy accounting of rhizomes and aboveground biomass. Rhizomes are more costly resource wise to produce than biomass. Miscanthus production is highly sustainable using 64–70% renewable resources. Biomass energy content at the pellet plant is 89 times the energy input required.